Normal tissue radioprotection by amifostine via Warburg-type effects - Michael I. Koukourakis; Alexandra Giatromanolaki; Christos E. Zois; Dimitra Kalamida; Stamatia Pouliliou; Ilias V. Karagounis; Tzu-Lan Yeh; Martine I. Abboud; Timothy D. W. Claridge; Christopher J. Schofield; Efthimios Sivridis; Costantinos Simopoulos; et al. (Scientific Reports)
Abstract The mechanism of Amifostine (WR-2721) mediated radioprotection is poorly understood. The effects of amifostine on human basal metabolism, mouse liver metabolism and on normal and tumor hepatic cells were studied. Indirect calorimetric canopy tests showed significant reductions in oxygen consumption and of carbon dioxide emission in cancer patients receiving amifostine. Glucose levels significantly decreased and lactate levels increased in patient venous blood. Although amifostine in vitro did not inhibit the activity of the prolyl-hydroxylase PHD2, experiments with mouse liver showed that on a short timescale WR-1065 induced expression of the Hypoxia Inducible Factor HIF1α, lactate dehydrogenase LDH5, glucose transporter GLUT2, phosphorylated pyruvate dehydrogenase pPDH and PDH-kinase. This effect was confirmed on normal mouse NCTC hepatocytes, but not on hepatoma cells. A sharp reduction of acetyl-CoA and ATP levels in NCTC cells indicated reduced mitochondrial usage of pyruvate. Transient changes of mitochondrial membrane potential and reactive oxygen species ROS production were evident. Amifostine selectively protects NCTC cells against radiation, whilst HepG2 neoplastic cells are sensitized. The radiation protection was correlates with HIF levels. These findings shed new light on the mechanism of amifostine cytoprotection and encourage clinical research with this agent for the treatment of primary and metastatic liver cancer.